SOURCE ANALYSIS OF NURUDDIN SOBUNI’S BOOK ‘AL-MUNTAQA MIN ISMAT AL-ANBIYA - Akhmedov Anvar (Journals Park Publishing, 2025)
Nuruddin Sabuni, one of the important representatives of the Moturidiyyah doctrine, opposed the erroneous categories of belief that were active in his time and defended the belief of pure Ahli Sunnah. He explained the difficult-to-understand issues in kalam in an understandable language. In this regard, it is appropriate to note that mutakallim has a thorough knowledge of Arabic and Persian languages.
Keywords: kalam, aqaid, ‘al-Muntaka’ work, Nuriddin Sabuni, prophets.